Rasch Analysis: Academic Resilience Of Students Based On Gender - Fatma Nofriza; Chandra Dewi Sukma Wardani; Dony Darma Sagita (STKIP Andi Matappa, 2020)
This study aims to determine the differences in academic resilience between male and female students at UHAMKA that analyzed through the rash model. This study uses a comparative descriptive approach, the sample in this study amounted to 333 students consisting of 255 women and 78 men who were obtained by means of sampling convenience. The instrument used was ARS-30 (The 30 item Academic Resilience Scale), the data analysis technique was an independent t-test with the help of the SPSS application and combined with the Rasch model stacking that was tested. The results of this study indicate the value of sig. 2 Talled of 0.94> 0.05, it can be concluded that there is no significant difference between the resilience levels of male and female students. Furthermore, partial resilience of men and women are both in the medium category.